Uproszczone metody opodatkowania przedsiębiorców podatkiem od wartości dodanej w Niemczech - Hybka, Małgorzata Magdalena (Simplified Methods Of Vat Calculation For Entrepreneurs In Germany, 2008)
The main objective of this article is to provide an overview of the regulations related to special schemes in Germany. In accordance with selected provisions of the Council Directive 2006/112/EC, Member States may apply this schemes to certain transactions or certain categories of taxable person. They concern especially small enterprises and are aimed at simplification of the tax calculation. The author analyzes the data published by German Statistical Office and provides information about the number, turnover and tax paid by the mentioned entrepreneurs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 223-230